Ligamentous Reconstruction of the Knee: What Orthopaedic Surgeons Want Radiologists to Know - Geeslin, Andrew G.; Geeslin, Matthew G.; LaPrade, Robert F. (Seminars in Musculoskeletal Radiology, 2017)
Knee ligament injuries are common, and treatment methods are continually evolving. Accurate clinical diagnosis with imaging confirmation is critical to support appropriate treatment. Several imaging pearls allow for improved recognition of injuries. Stress radiographs may be obtained to quantify knee laxity. Magnetic resonance imaging allows assessment of the complex anatomy of the knee and has excellent sensitivity and specificity for many injuries.
Keywords: knee ligaments; stress radiographs; anterior cruciate ligament; posterior cruciate ligament; medical collateral ligament; posterolateral knee; magnetic resonance imaging